A positive electrode sheet and lithium ion battery
By controlling the particle size of lithium manganese iron phosphate particles and the tensile strength and compaction density of the positive electrode sheet, the problems of poor conductivity and kinetic performance of lithium manganese iron phosphate materials are solved, and the fast charging performance and high performance of the positive electrode sheet are achieved Energy density.
Patent Information
- Application Number
- CN202411436264.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-10-15
AI Technical Summary
The electron and ion transport impedances in lithium manganese iron phosphate materials are large, and the material conductivity and kinetic properties are poor, which leads to the prolonging of the diffusion path of the lithium ion, affecting the dynamic performance of the battery. The specific surface area of the particle is too large after the primary particle size decreases, resulting in slurry. The material solid content and the coating density are low, which are not conducive to the increase of the energy density of the battery cell.
By controlling the D90 particle size of lithium manganese iron phosphate particles, the tensile strength and compaction density of the positive electrode sheet, it ensures that it meets a specific relationship (1600 < D90/PD × σ < 4800), to improve the performance of the positive electrode sheet, combined with Suitable foil and processing technology to prepare positive electrode sheets with fast charging performance and high energy density.
The excellent fast charging performance and high energy density of the positive electrode sheet are achieved, scratches caused by excessive particle size and poor processability caused by excessive small size, and the dynamic performance and energy density of the battery are improved.
Smart Images

Figure CN118943295B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion battery positive electrode sheets, and relates to a positive electrode sheet and a lithium ion battery, and in particular to a lithium iron manganese phosphate positive electrode sheet and a lithium ion battery. Background Art
[0002] In lithium iron manganese phosphate materials, the electron and ion transmission impedance is large, and the material conductivity and dynamic performance are poor. Among them, the solid phase diffusion of lithium ions in lithium iron manganese phosphate materials becomes a key factor restricting its dynamics. Therefore, from the perspective of shortening the lithium ion diffusion path, reducing the primary particle size is helpful to improve the dynamic performance of lithium iron manganese phosphate materials. However, if the primary particle size is reduced to a certain extent, the specific surface area of the particles will be too large, and the solvent and binder required to make the particles evenly dispersed during the slurrying process will also increase, further resulting in a low solid content of the slurry, and cracking is prone to occur during the thick electrode coating process, resulting in low coating surface density, which is not conducive to the improvement of the energy density of the battery cell.
[0003] Therefore, how to design a more suitable lithium iron manganese phosphate positive electrode plate to solve the above-mentioned problems of the existing lithium iron manganese phosphate positive electrode has become one of the focuses of widespread attention of many technical personnel in the industry. Summary of the invention
[0004] In view of this, the technical problem to be solved by the present invention is to provide a positive electrode sheet and a preparation method thereof, a lithium ion battery, and in particular a lithium iron manganese phosphate positive electrode sheet. The lithium iron manganese phosphate positive electrode sheet provided by the present invention satisfies a specific relationship, and the performance of the lithium iron manganese phosphate positive electrode sheet is further improved by controlling the tensile strength of the lithium iron manganese phosphate particles and the positive electrode sheet and the compaction density of the positive electrode sheet.
[0005] A first aspect of the present invention provides a positive electrode sheet, the positive electrode sheet comprising a current collector and a positive electrode material composited on the current collector;
[0006] The positive electrode material includes a positive electrode active material;
[0007] The positive electrode active material is selected from lithium manganese iron phosphate;
[0008] The D90 particle size of the lithium manganese iron phosphate particles, the tensile strength σ of the positive electrode sheet, and the compaction density PD of the positive electrode sheet satisfy the relationship described in formula (I):
[0009] 1600 <D90 / PD×σ<4800 (I);
[0010] The unit of D90 is μm, the unit of σ is MPa, and the unit of PD is g / cm 3 .
[0011] Preferably, in the formula (I), 2000 < D90 / PD×σ < 4000.
[0012] Preferably, the lithium iron manganese phosphate particles specifically include lithium iron manganese phosphate secondary particles.
[0013] Preferably, the D90 particle size of the lithium iron manganese phosphate particles is 10 - 50 μm.
[0014] Preferably, the D90 particle size of the lithium iron manganese phosphate particles is 15 - 40 μm.
[0015] Preferably, the tap density PD is 2.0 - 2.5 g / cm 3 .
[0016] Preferably, the tensile strength σ is 100 - 500 MPa.
[0017] Preferably, the compaction change rate △PD of the positive electrode sheet and the tensile strength σ of the positive electrode sheet satisfy the relational expression described in formula (II):
[0018] 0 < σ×△PD < 95 (II);
[0019] wherein, the unit of σ is MPa, and △PD = (PD max - PD) / PD, and PD max is the maximum tap density;
[0020] The maximum tap density is the tap density corresponding to the light transmission when the positive electrode sheet is folded in half after secondary rolling.
[0021] Preferably, the range of △PD is 4% - 25%.
[0022] The second aspect of the present invention also provides a lithium ion battery, including a positive electrode sheet;
[0023] The positive electrode sheet is the positive electrode sheet described in any one of the above technical solutions.
[0024] The present invention provides a positive electrode sheet, which includes a current collector and a positive electrode material compounded on the current collector; the positive electrode material includes a positive electrode active material; the positive electrode active material is selected from lithium iron manganese phosphate; the D90 particle size of the lithium iron manganese phosphate particles, the tensile strength σ of the positive electrode sheet, and the tap density PD of the positive electrode sheet satisfy the relational expression described in formula (I): 1600 < D90 / PD×σ < 4800 (I). Compared with the prior art, the positive electrode sheet of the present invention balances the D90 particle size of the lithium iron manganese phosphate particles, the tensile strength σ of the positive electrode sheet, and the tap density PD of the positive electrode sheet, so that the positive electrode sheet has both excellent fast charging performance and energy density. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a 1000X SEM photo of the lithium iron manganese phosphate pole piece after rolling provided by the present invention;
[0026] Figure 2 This is a 3000X SEM photograph of the lithium manganese iron phosphate pole piece provided by the present invention after rolling. DETAILED DESCRIPTION
[0027] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention rather than limiting the patent claims of the present invention.
[0028] All raw materials of the present invention have no particular limitation on their sources, and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.
[0029] There is no particular restriction on the purity of all raw materials in the present invention. The present invention preferably uses analytically pure materials or materials with conventional purity requirements in the field of lithium-ion battery positive electrode sheet material preparation.
[0030] The brands and abbreviations of all raw materials of the present invention are conventional brands and abbreviations in the art. Each brand and abbreviation is clear and definite in the field of its related use. Those skilled in the art can purchase them from the market or prepare them by conventional methods according to the brands, abbreviations and corresponding uses.
[0031] The abbreviations of the processes used in the present invention are all conventional abbreviations in the field. The specific steps and conventional parameters of each abbreviation are clear and definite in its relevant field. Those skilled in the art can implement them in a conventional manner based on the abbreviations.
[0032] Particle size D90 of lithium manganese iron phosphate particles: In the particle size distribution, the particle size value corresponding to the cumulative distribution percentage from small to large reaches 90%.
[0033] Tensile strength of positive electrode sheet (σ): In the tensile test, the maximum tensile stress to which the sample is subjected until it breaks is the tensile strength, and the result is expressed in MPa.
[0034] The compaction change rate of the positive electrode sheet after re-pressurization △PD: The compaction of the positive electrode sheet after re-rolling after disassembly, relative to the degree of change in compaction before rolling, the unit is %.
[0035] The present invention provides a positive electrode sheet, the positive electrode sheet comprising a current collector and a positive electrode material composited on the current collector;
[0036] The positive electrode material includes a positive electrode active material;
[0037] The positive electrode active material is selected from lithium manganese iron phosphate;
[0038] The D90 particle size of the lithium manganese iron phosphate particles, the tensile strength σ of the positive electrode sheet, and the compaction density PD of the positive electrode sheet satisfy the relationship described in formula (I):
[0039] 1600 <D90 / PD×σ<4800 (I);
[0040] The unit of D90 is μm, the unit of σ is MPa, and the unit of PD is g / cm 3 .
[0041] The present invention believes that although the agglomerate solution can reduce the content of solvent and binder in the slurry mixing process, it takes into account the reduction of primary particle size and thick electrode coating. However, the agglomerate will cause a larger particle size, and it is not easy to achieve a higher compaction density during the processing, which is not conducive to the improvement of the energy density of the battery cell. Therefore, it is necessary to solve the problem of improving the compaction density of the lithium iron manganese phosphate agglomerate electrode sheet. The present invention specially designs a lithium iron manganese phosphate positive electrode sheet with a specific structure. The D90 particle size of the lithium iron manganese phosphate particles in the positive electrode sheet, the tensile strength σ of the positive electrode sheet, and the compaction density PD of the positive electrode sheet satisfy a specific relationship. The present invention further improves the performance of the lithium iron manganese phosphate positive electrode sheet by controlling the lithium iron manganese phosphate particles, the tensile strength of the positive electrode sheet, and the compaction density of the positive electrode sheet.
[0042] The present invention comprehensively relates the tensile strength of the pole piece of the lithium iron manganese phosphate agglomerate to the particle size distribution of the particles and the pole piece state corresponding to the high compaction, wherein the pole piece tensile strength is related to the performance of the current collector (foil), the performance of the active material layer, and the processing technology / equipment. In the present invention, when D90, σ, and PD satisfy the present relationship (I), under a certain compaction density, the pole piece tensile strength prepared by using lithium iron manganese phosphate agglomerates with relatively large particle sizes, coordinated with suitable foils and processing technologies is low; the pole piece tensile strength prepared by using lithium iron manganese phosphate agglomerates with relatively small particle sizes, coordinated with suitable foils and processing technologies is high; under the condition of a certain particle size, the pole piece tensile strength prepared by using a larger compaction density, coordinated with suitable foils and processing technologies is high; the pole piece tensile strength prepared by using a lower compaction density, coordinated with suitable foils and processing technologies is low. Further, compared with the lithium iron manganese phosphate particles, D50 reflects the overall particle size of the particles, while D90 can better reflect the size characteristics of large particles in the lithium iron manganese phosphate material. If the upper limit of D90 is exceeded, the particle size is too large, which may easily cause scratches on the electrode during coating and require higher strength of the foil during rolling. If the lower limit of D90 is exceeded, the particle size is too small, more solvent and binder are required during slurry mixing, and the processing performance of the slurry deteriorates, which is not conducive to thick electrode coating.
[0043] Moreover, the tensile strength of the electrode tab is related to the properties of the current collector (foil), the properties of the active material layer, and the processing technology, especially the foil, the coating amount (areal density) of the active material, and the adhesion between the active material layer and the foil. If the tensile strength σ is too low, it indicates the deterioration of the processability of the electrode tab after rolling, which may lead to negative impacts such as breakage of the electrode tab during the rolling process. In addition, there may be some microcracks inside the current collector, affecting electron transport and thus the performance of the battery cell.
[0044] In the present invention, in the relational expression of formula (I), 2000 < D90 / PD × σ < 4000 is possible, and 2500 < D90 / PD × σ < 3500 is also possible.
[0045] In the present invention, the lithium iron manganese phosphate particles are specifically preferably lithium iron manganese phosphate secondary particles.
[0046] In the present invention, the D90 particle size of the lithium iron manganese phosphate particles is preferably 10 - 50 μm, more preferably 15 - 40 μm, still more preferably 20 - 35 μm, and even more preferably 25 - 30 μm.
[0047] In the present invention, the tap density PD is preferably 2.0 - 2.5 g / cm 3 , more preferably 2.1 - 2.4 g / cm 3 , still more preferably 2.2 - 2.3 g / cm 3 .
[0048] In the present invention, the tensile strength σ is preferably 100 - 500 MPa, more preferably 150 - 450 MPa, still more preferably 200 - 400 MPa, and even more preferably 250 - 350 MPa.
[0049] In the present invention, the compaction change rate △PD of the positive electrode tab and the tensile strength σ of the positive electrode tab preferably satisfy the relational expression of formula (II):
[0050] 0 < σ × △PD < 95 (II);
[0051] wherein, the unit of σ is MPa, △PD = (PD max - PD) / PD, and PD max is the maximum compaction density;
[0052] In the present invention, the maximum compaction density is preferably the compaction density corresponding to the light transmission when the positive electrode tab is folded in half after secondary rolling or the compaction density corresponding to the crushing of the lithium iron manganese phosphate particles after secondary rolling of the positive electrode tab.
[0053] In the present invention, in formula (II), σ × △PD can also be 5 - 90, or 15 - 80, or 35 - 60.
[0054] In the present invention, the range of ΔPD is preferably 4% to 25%, more preferably 5% to 23%, more preferably 8% to 20%, and more preferably 10% to 18%.
[0055] The present invention provides a method for preparing a positive electrode sheet, comprising the following steps:
[0056] 1) Mixing the lithium manganese iron phosphate aggregate secondary particles, a binder, a conductive agent and a solvent to obtain a positive electrode slurry;
[0057] 2) The positive electrode slurry obtained in the above steps is coated on the current collector, and then rolled to obtain a positive electrode sheet.
[0058] The present invention firstly mixes the lithium manganese iron phosphate aggregate secondary particles, a binder, a conductive agent and a solvent to obtain a positive electrode slurry.
[0059] In the present invention, the method for preparing the lithium iron manganese phosphate aggregate secondary particles preferably comprises the following steps:
[0060] (1) After ball-milling and mixing the manganese source, iron source, carbon source, lithium source and phosphorus source, a precursor powder is obtained after a grinding, a spray drying and a sintering;
[0061] (2) The precursor powder obtained in the above step and the carbon source are ball-milled again, and then subjected to secondary grinding, secondary spraying and secondary sintering to obtain secondary particles of lithium manganese iron phosphate agglomerates.
[0062] In the present invention, the sintering process of the lithium iron manganese phosphate agglomerate secondary particles is specifically to carry out sintering under a protective atmosphere.
[0063] In the present invention, the pressure of the primary spray is preferably 0.1 to 1.35 MPa, more preferably 0.1 to 1.35 MPa, more preferably 0.5 to 1.3 MPa, and more preferably 1 to 1.2 MPa.
[0064] In the present invention, the carbon content of the primary spray coating is preferably 0.1%wt~0.8%wt, more preferably 0.2%wt~0.7%wt, and more preferably 0.3%wt~0.6%wt.
[0065] In the present invention, the primary sintering time is preferably 1 to 10 hours, more preferably 3 to 8 hours, and more preferably 5 to 6 hours.
[0066] In the present invention, the primary sintering temperature is preferably 200-800°C, more preferably 300-700°C, and even more preferably 400-600°C.
[0067] In the present invention, the carbon content of the secondary spray coating is preferably 1.0%wt~3.0%wt, more preferably 1.2%wt~2.8%wt, and more preferably 1.5%wt~2.5%wt.
[0068] In the present invention, the pressure of the secondary spray is preferably 0.1-1.35 MPa, more preferably 0.1-1.35 MPa, more preferably 0.5-1.3 MPa, and more preferably 1-1.2 MPa.
[0069] In the present invention, the secondary sintering time is 1 to 10 hours, more preferably 3 to 8 hours, and more preferably 5 to 6 hours.
[0070] In the present invention, the temperature of the secondary sintering is 400-800°C, more preferably 450-750°C, and more preferably 500-700°C.
[0071] In the present invention, the secondary spraying is specifically, preferably adding a flux and a dispersant for secondary spraying;
[0072] In the present invention, the amount (mass content) of the flux added is preferably 0.1% to 1.5%, more preferably 0.3% to 1.2%, and more preferably 0.5% to 1.0%.
[0073] In the present invention, the added amount (mass content) of the dispersant A is preferably 0.1% to 1.3%, more preferably 0.3% to 1.1%, and more preferably 0.5% to 0.8%.
[0074] In the present invention, the method for preparing the lithium iron manganese phosphate aggregate secondary particles preferably comprises the following steps:
[0075] (1) Grinding and mixing a manganese source, an iron source, a carbon source, a lithium source, a phosphorus source and water, and then spray drying and sintering to obtain a precursor powder;
[0076] (2) Under a protective atmosphere, the precursor powder obtained in the above step is ball-milled again with a carbon source and water, and then subjected to secondary spraying and secondary sintering under a protective atmosphere to obtain secondary particles of lithium manganese iron phosphate agglomerates.
[0077] In the present invention, the sintering process of the lithium iron manganese phosphate agglomerate secondary particles is specifically to carry out sintering under a protective atmosphere.
[0078] In the present invention, the pressure of the primary spray is preferably 0.3-1.25 MPa, more preferably 0.5-1.0 MPa, and more preferably 0.7-0.8 MPa.
[0079] In the present invention, the carbon content of the primary spray coating is preferably 0.2%wt~0.7%wt, more preferably 0.3%wt~0.6%wt, and more preferably 0.4%wt~0.5%wt.
[0080] In the present invention, the primary sintering time is preferably 2 to 8 hours, more preferably 3 to 7 hours, and more preferably 4 to 6 hours.
[0081] In the present invention, the primary sintering temperature is preferably 300-600°C, more preferably 350-550°C, and even more preferably 400-500°C.
[0082] In the present invention, the carbon content of the secondary spray coating is preferably 1.2%wt~3.0%wt, more preferably 1.5%wt~2.8%wt, more preferably 1.8%wt~2.5%wt.
[0083] In the present invention, the pressure of the secondary spray is preferably 0.3-1.25 MPa, more preferably 0.5-1.05 MPa, and more preferably 0.7-0.9 MPa.
[0084] In the present invention, the secondary sintering time is 2 to 11 hours, more preferably 4 to 9 hours, and more preferably 6 to 7 hours.
[0085] In the present invention, the secondary sintering temperature is 500-700°C, more preferably 550-650°C.
[0086] In the present invention, the secondary spraying is specifically, preferably adding a flux and a dispersant for secondary spraying;
[0087] In the present invention, the amount (mass content) of the flux added is preferably 0.05% to 1.4%, more preferably 0.3% to 1.2%, and more preferably 0.5% to 1.0%.
[0088] In the present invention, the added amount (mass content) of the dispersant A is preferably 0.01% to 1.0%, more preferably 0.05% to 0.8%, and more preferably 0.1% to 0.5%.
[0089] In the present invention, the positive electrode slurry obtained in the above steps is finally coated on the current collector, and then rolled to obtain a positive electrode sheet.
[0090] The present invention provides a lithium ion battery, comprising a positive electrode sheet;
[0091] The positive electrode sheet is the positive electrode sheet described in any one of the above technical solutions or the positive electrode sheet prepared by the preparation method described in any one of the above technical solutions.
[0092] The present invention is to complete and refine the overall technical solution, and better ensure that the positive electrode sheet satisfies the relationship described in formula (I). The above-mentioned lithium iron manganese phosphate positive electrode sheet and its preparation method, and lithium ion battery may specifically include the following contents:
[0093] A battery includes a positive electrode sheet, the positive electrode sheet includes a positive electrode material, the positive electrode active material includes lithium manganese iron phosphate particles, the particle size D90 of the lithium manganese iron phosphate particles, and the tensile strength (denoted as σ) and compaction (denoted as PD) of the positive electrode sheet, D90 and σ, PD satisfy the following relationship (I): 1600 <D90 / PD×σ<4800。
[0094] In the present invention, under certain compaction density conditions, the larger the D90, the more large particles exist. Large particles will cause damage to foil materials and the like during rolling. The pole pieces made under certain compaction conditions have low tensile strength. Therefore, it is necessary to improve the tensile strength of the pole pieces by combining other conditions to avoid pole piece breakage in subsequent processes such as winding.
[0095] In the present invention, when the lower limit of the relationship is exceeded, D90 is too small, resulting in too large specific surface area, poor slurry processability, too many interface side reactions, and thus accelerated capacity decay and DCR growth in long-term cycling or storage, or the tensile strength of the pole piece is too low to meet the processing requirements, or the compaction of the pole piece is too large, resulting in cracking of the agglomerate material and poor conductivity between primary particles, affecting the kinetic performance of the battery; when the upper limit of the relationship is exceeded, D90 is too large, resulting in easy scratches on the pole piece during coating, and higher strength requirements for the foil during rolling, or the compaction of the pole piece is too low, the battery energy density is low, and the ohmic contact between the agglomerate particles is poor, affecting the kinetic performance of the battery; or the tensile strength of the pole piece is large, and higher strength requirements for the foil are required.
[0096] Specifically, the lithium manganese iron phosphate is an agglomerate including a plurality of primary particles.
[0097] Specifically, the D90 range of lithium manganese iron phosphate particles is: 10~50μm.
[0098] Specifically, the PD range is 2.0~2.5. The larger the PD, the higher the energy density of the battery. If the PD is too large, the agglomerate particles are crushed, the conductivity between the primary particles becomes poor, which is not conducive to the dynamic performance. At the same time, the current collector is over-pressed, and the pole piece after rolling is easy to break, which is not conducive to processing. If the PD is too small, the battery energy density is low. At the same time, the contact resistance between the agglomerate particles is large, and the electronic conductivity is low, which is also not conducive to the dynamic performance.
[0099] Specifically, the tensile strength σ of the positive electrode sheet ranges from 100 to 500 MPa.
[0100] Specifically, the compaction change rate △PD (the compaction of the disassembled positive electrode sheet after rolling again, relative to the degree of change in compaction before rolling, the compaction change rate △PD) and the tensile strength σ of the positive electrode sheet satisfy the following relationship (II):
[0101] 0<σ×△PD<95. Formula (II) reflects the particle strength / agglomeration degree matching.
[0102] In the present invention, the tensile strength σ is the tensile strength of the electrode under the initial compaction conditions, in MPa, △PD is the maximum compaction change rate of the electrode, △PD = (PDmax-PD) / PD, PDmax is the maximum compaction value corresponding to the light transmittance of the electrode after rolling again, or the crushing of agglomerate particles, and particle crushing is defined as a decrease in the D90 change rate of the original positive electrode particles by more than 20%.
[0103] Among them, the larger the △PD is, the higher the particle strength of the pole piece is, and the higher the strength and toughness of the pole piece / aluminum foil are.
[0104] Specifically, the compaction change rate △PD of the positive electrode sheet after re-pressurization ranges from 4% to 25%.
[0105] In the present invention, PD, PD max And the detection method of σ specifically includes the following steps:
[0106] PD:
[0107] 1. Actual surface density a of the pole piece before rolling,
[0108] 2. According to the material powder compaction b, according to the design compaction, the corresponding thickness of the electrode under the corresponding compaction gradient is calculated c = a / (b+0.1) + foil thickness. According to the calculated thickness of the electrode under different compactions, after adjusting the appropriate pressure of the roller press, the electrode is rolled by the roller press.
[0109] With the same folding force, after the electrode is folded once, the folded part is compared with the bright light. If there is no light transmission at the middle fold seam, the number of folds will be increased. After two folds, there is one light transmission at the fold seam, which is the actual compaction of the electrode group; the actual compaction of the electrode d = the density of the electrode after rolling / (the thickness of the electrode after rolling - the thickness of the foil)
[0110] △PD=(PD max -PD) / PD, PD max is the maximum compaction density;
[0111] In the present invention, the maximum compaction density PD max It is the compaction density corresponding to the positive electrode sheet when it is folded in half and transparent to light after being rolled twice.
[0112] Specific test conditions: After the positive electrode sheet is rolled once normally, the compaction PD of the positive electrode sheet under the first rolling is obtained, and then the positive electrode sheet is rolled twice to obtain the maximum compaction PD of the positive electrode sheet under the second rolling. max The specific restriction is that the positive electrode sheet cannot break under the secondary rolling.
[0113] The specific test conditions are shown in Table 1.
[0114] σ:
[0115] 1. Use a utility knife to cut off a 50cm positive electrode sheet.
[0116] 2 Place the positive electrode sheet on the thin film sample making machine and cut it into several strips with a length of 100 mm and a width of 150 mm in the MD and TD directions.
[0117] 3 Clamp the positive electrode strip on the pneumatic fixture of the universal testing machine. At this time, the gauge length between the fixtures is 100mm.
[0118] 4 The universal testing machine was used for stretching at a speed of 100 mm / min.
[0119] 5 After the universal testing machine stops, open the pneumatic clamp, clean the diaphragm debris, and adjust the gauge length to the initial length again.
[0120] 6 Record the tensile strength and elongation at break results displayed on the instrument program.
[0121] 7 Repeat steps 1 to 6, take the arithmetic mean of the results, and retain one decimal place.
[0122] See also Figure 1 , Figure 1 This is a 1000X SEM photograph of the lithium manganese iron phosphate pole piece provided by the present invention after rolling.
[0123] See also Figure 2 , Figure 2 This is a 3000X SEM photograph of the lithium manganese iron phosphate pole piece provided by the present invention after rolling.
[0124] The present invention also provides a method for preparing a lithium iron manganese phosphate lithium ion battery, comprising the following steps:
[0125] 1) Preparation of positive electrode material 1: Mix the manganese source, iron source, carbon source, lithium source and phosphorus source, ball mill evenly (adjust the manganese-iron ratio of the agglomerate according to the molar ratio of the manganese source and the iron source), and spray dry to obtain a precursor powder;
[0126] The precursor powder, carbon source, doping source (additives, etc. may also be added) are mixed and ball-milled for a second time. The material is sprayed once and then sintered at a high temperature for a period of time, and then sprayed and sintered again (the particle size is controlled by the sintering temperature) to obtain lithium manganese iron phosphate agglomerate particles.
[0127] Preparation of positive electrode material 2: Add manganese source, iron source, carbon source, lithium source and phosphorus source to deionized water, mix, dry and crush to obtain a precursor, spray the precursor once, sinter in a nitrogen atmosphere to obtain a calcined sample, mix the calcined sample, carbon source and deionized water, ball mill, dry, crush, spray twice and sinter twice in a nitrogen atmosphere to obtain manganese iron phosphate lithium agglomerate particles.
[0128] 2) Preparation of positive electrode sheet: According to the mass ratio (94~97.5:1.5~4.0:0.8~1.2:0.2~0.8), the above-mentioned lithium manganese iron phosphate agglomerate is used as the main material, mixed evenly with the binder PVDF, the conductive agent SP, and the conductive agent, and dispersed in the solvent to obtain a positive electrode slurry; the positive electrode slurry is coated on aluminum foil to obtain a double-sided coated positive electrode sheet; then, the positive electrode sheet is obtained by rolling and cutting.
[0129] 3) Preparation of negative electrode sheet: natural graphite, artificial graphite, mesophase carbon microspheres, hard carbon, soft carbon, silicon, SiO x , Silicon Carbon, Li4Ti5O 12 One or more of the above-mentioned materials are uniformly mixed with the conductive agent SP, the binder CMC and the binder in a certain mass ratio, and dispersed in deionized water to obtain a negative electrode slurry; the negative electrode slurry is coated on a copper foil to obtain a single-sided coated electrode sheet; and then rolled and cut to obtain a negative electrode sheet.
[0130] 4) Preparation of electrolyte
[0131] Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L. (The specific electrolyte solvent is adjusted according to actual conditions)
[0132] 5) Preparation of isolation membrane
[0133] Select one of PP, PE, PP / PF as the isolation film. (The isolation film selection can also be adjusted according to actual conditions)
[0134] 6) Assembly and formation
[0135] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.
[0136] The above content of the present invention provides a lithium iron manganese phosphate positive electrode sheet and a preparation method thereof, and a lithium ion battery. The present invention specially designs a lithium iron manganese phosphate positive electrode sheet with a specific structure, and the D90 particle size of the lithium iron manganese phosphate particles in the positive electrode sheet, the tensile strength σ of the positive electrode sheet, and the compaction density PD of the positive electrode sheet satisfy a specific relationship. The present invention further improves the performance of the lithium iron manganese phosphate positive electrode sheet by controlling the tensile strength of the lithium iron manganese phosphate particles, the positive electrode sheet, and the compaction density of the positive electrode sheet.
[0137] The present invention comprehensively relates the tensile strength of the pole piece of manganese iron phosphate lithium agglomerate to the particle size distribution of the particles and the pole piece state corresponding to the high compaction, wherein the pole piece tensile strength is related to the performance of the current collector (foil), the performance of the active material layer, and the processing technology / equipment. In the present invention, when D90, σ, and PD satisfy the present relationship (I), under a certain compaction density, the pole piece tensile strength prepared by using manganese iron lithium agglomerates with relatively large particle sizes, coordinated with suitable foils and processing technologies, is relatively low; or the pole piece tensile strength prepared by using manganese iron lithium agglomerates with relatively small particle sizes, coordinated with suitable foils and processing technologies, is relatively high; under the condition of a certain particle size, to obtain a larger compaction density, a suitable foil and processing technology are used, and the pole piece tensile strength is relatively high; under a lower compaction density, a suitable foil and processing technology are used, and the pole piece tensile strength is relatively low. When the lower limit of the relationship is exceeded, the tensile strength of the pole piece is too low and cannot meet the processing requirements. Furthermore, compared with the D50 of lithium iron manganese phosphate particles, which reflects the overall particle size of the particles, D90 can better reflect the size characteristics of large particles in lithium iron manganese phosphate materials. If the upper limit of D90 is exceeded, the particle size is too large, which is easy to cause scratches on the pole piece during coating, and the strength requirements of the foil are high during rolling; when the lower limit of D90 is exceeded, the particle size is too small, more solvents and binders are required during slurry mixing, and the processing performance of the slurry is deteriorated, which is not conducive to thick electrode coating.
[0138] Moreover, the tensile strength of the pole piece is related to the performance of the current collector (foil), the performance of the active material layer, and the processing technology, especially the foil, the amount of active material coating (surface density), and the bonding between the active material layer and the foil. If the tensile strength σ is too low, it means that the processing of the pole piece after rolling is deteriorated, which may lead to negative effects such as the pole piece breaking during the rolling process. In addition, there may be some microcracks inside the current collector, which will affect the electron transmission and thus the performance of the battery cell.
[0139] Furthermore, the present invention also provides a relationship (II), and the compaction change rate △PD reflects the particle strength and agglomeration of the lithium iron manganese phosphate particles. By simultaneously controlling △PD and tensile strength σ, it is helpful to achieve the energy density of the battery while maintaining good processability. When the upper limit of the relationship is exceeded, △PD is too large, indicating that the initial compaction is too low, which is not conducive to the realization of high energy density of the battery, or the tensile strength of the pole piece is too high, and the requirements for aluminum foil are too high. Moreover, a certain △PD indicates that the lithium iron manganese phosphate particles have a suitable agglomeration condition. If it is too high, it means that the particle strength of the lithium iron manganese phosphate particles is low, and under greater pressure conditions, the agglomerates are easily crushed; if it is too low, it means that the lithium iron manganese phosphate particles are close to the limit compaction, the flexibility of the pole piece is too low, or the particles are close to being broken.
[0140] In order to further illustrate the present invention, a positive electrode sheet and a preparation method thereof, and a lithium-ion battery provided by the present invention are described in detail in combination with the following examples. However, it should be understood that these examples are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and specific operating processes are given only to further illustrate the features and advantages of the present invention, rather than to limit the claims of the present invention. The protection scope of the present invention is not limited to the following examples.
[0141] Example 1
[0142] 1) Preparation of positive electrode materials: manganese acetate, iron acetate, sucrose / polyvinyl alcohol, lithium carbonate, and ammonium dihydrogen phosphate are mixed according to n (manganese acetate + iron acetate), n (lithium carbonate), and n (ammonium dihydrogen phosphate) = 1:1:1, where n (manganese acetate): n (iron acetate) meets 3:1, and the mixture is ground evenly once, spray dried once, and sintered once to obtain a precursor powder; the precursor powder, sucrose / polyvinyl alcohol, magnesium chloride, and calcium chloride are mixed and ball milled twice. After the material is sprayed twice, it is sintered twice at high temperature for a period of time, and then sprayed twice and sintered twice to obtain manganese iron lithium phosphate agglomerate particles. The pressure of the spray equipment before the first and second sintering is 0.4Mpa, and the amount of flux (potassium carbonate) added in the second spray drying before the second sintering is 0.1%, and the dispersant (polyester polyether) is 0.05%.
[0143] 2) Preparation of positive electrode sheet: According to the mass ratio (94:3:1:2), the above-mentioned lithium manganese iron phosphate agglomerate is used as the main material, mixed evenly with the binder PVDF, the conductive agent SP, and the conductive agent, and dispersed in the solvent to obtain a positive electrode slurry; the positive electrode slurry is coated on aluminum foil to obtain a double-sided coated positive electrode sheet; then, the positive electrode sheet is obtained by rolling and cutting.
[0144] 3) Preparation of negative electrode sheet: artificial graphite is evenly mixed with conductive agent SP 4% and binder 4% in a mass ratio of 92%, and dispersed in deionized water to obtain negative electrode slurry; the negative electrode slurry is coated on copper foil to obtain a single-sided coated electrode sheet; then, the negative electrode sheet is obtained by rolling and cutting.
[0145] 4) Preparation of electrolyte
[0146] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L.
[0147] 5) Preparation of isolation film PP is selected as the isolation film.
[0148] 6) Assembly and formation
[0149] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.
[0150] Example 2
[0151] 1) Preparation of positive electrode materials: manganese acetate, iron acetate, sucrose / polyvinyl alcohol, lithium carbonate, and ammonium dihydrogen phosphate are mixed according to n (manganese acetate + iron acetate), n (lithium carbonate), and n (ammonium dihydrogen phosphate) = 1:1:1, where n (manganese acetate): n (iron acetate) satisfies 3:1, and ball milled evenly, and spray dried to obtain precursor powder; precursor powder, sucrose / polyvinyl alcohol, magnesium chloride, and calcium chloride are mixed and ball milled twice. After the material is sprayed once, it is sintered at high temperature for a period of time, and then sprayed and sintered twice to obtain manganese iron lithium phosphate agglomerate particles. The pressure of the spray equipment before the first and second sintering is 0.9Mpa, and the amount of flux (potassium carbonate) added in the second spray drying before the second sintering is 1.32%, and the dispersant (polyester polyether) is 0.4%.
[0152] 2) The positive electrode sheet was prepared in the same manner as in Example 1.
[0153] 3) The negative electrode sheet was prepared in the same manner as in Example 1.
[0154] 4) The preparation of the electrolyte is the same as in Example 1.
[0155] 5) The isolation film is selected from PE as the isolation film.
[0156] 6) Assembly and formation are the same as in Example 1.
[0157] Example 3
[0158] 1) Preparation of positive electrode materials: manganese acetate, iron acetate, sucrose / polyvinyl alcohol, lithium carbonate, and ammonium dihydrogen phosphate are mixed according to n (manganese acetate + iron acetate), n (lithium carbonate), n (ammonium dihydrogen phosphate) = 1:1:1, where n (manganese acetate): n (iron acetate) satisfies 3:1, ball milled evenly, and spray dried to obtain precursor powder; precursor powder, sucrose / polyvinyl alcohol, magnesium chloride, and calcium chloride are mixed and ball milled twice. After the material is sprayed once, it is sintered at high temperature for a period of time, and then sprayed and sintered twice to obtain manganese iron lithium phosphate agglomerate particles. The pressure of the spray equipment before the first and second sintering is 0.65Mpa, and the amount of flux (potassium carbonate) added in the second spray drying before the second sintering is 0.3%, and the dispersant (polyester polyether) is 0%.
[0159] 2) The positive electrode sheet was prepared in the same manner as in Example 1.
[0160] 3) The negative electrode sheet was prepared in the same manner as in Example 1.
[0161] 4) The preparation of the electrolyte is the same as in Example 1.
[0162] 5) The isolation film is selected from PP / PF as the isolation film.
[0163] 6) Assembly and formation are the same as in Example 1.
[0164] Example 4
[0165] 1) Preparation of positive electrode materials: manganese acetate, iron acetate, sucrose / polyvinyl alcohol, lithium carbonate, and ammonium dihydrogen phosphate are mixed according to n (manganese acetate + iron acetate), n (lithium carbonate), and n (ammonium dihydrogen phosphate) = 1:1:1, where n (manganese acetate): n (iron acetate) satisfies 3:1, and then dried and crushed to obtain a precursor. The precursor is sprayed once and sintered in a nitrogen atmosphere to obtain a sintered sample. The sintered sample, carbon source, and deionized water are mixed and ball-milled, dried, crushed, and sintered in a nitrogen atmosphere after a second spray. After crushing, lithium manganese iron phosphate agglomerate particles are obtained. The pressure of the spray equipment before the first and second sintering is 1.05Mpa. The amount of flux (potassium carbonate) added in the second spray drying before the second sintering is 1.28%, and the dispersant (polyester polyether) is 0.3%. The amount of flux and dispersant added is based on the mass of lithium manganese iron phosphate powder after the first sintering.
[0166] 2) The positive electrode sheet was prepared in the same manner as in Example 1.
[0167] 3) The negative electrode sheet was prepared in the same manner as in Example 1.
[0168] 4) The preparation of the electrolyte is the same as in Example 1.
[0169] 5) Preparation of isolation film: PP is selected as the isolation film.
[0170] 6) Assembly and formation are the same as in Example 1.
[0171] Example 5
[0172] Preparation of positive electrode materials: manganese acetate, iron acetate, sucrose / polyvinyl alcohol, lithium carbonate, and ammonium dihydrogen phosphate are mixed according to n (manganese acetate + iron acetate), n (lithium carbonate), and n (ammonium dihydrogen phosphate) = 1:1:1, where n (manganese acetate): n (iron acetate) satisfies 3:1, and deionized water is added to mix, dried, and crushed to obtain a precursor. The precursor is sprayed once, and then sintered in a nitrogen atmosphere to obtain a sintered sample. The sintered sample, carbon source, and deionized water are mixed and ball-milled, dried, crushed, and sintered in a nitrogen atmosphere after a second spray. After crushing, manganese iron lithium phosphate agglomerate particles are obtained. The pressure of the spray equipment before the first and second sintering is 0.82Mpa, and the amount of flux (potassium carbonate) added in the second spray drying before the second sintering is 1.4%, and the dispersant (polyester polyether) is 0.8%.
[0173] 2) The positive electrode sheet was prepared in the same manner as in Example 1.
[0174] 3) The negative electrode sheet was prepared in the same manner as in Example 1.
[0175] 4) The preparation of the electrolyte is the same as in Example 1.
[0176] 5) Preparation of isolation membrane: PE is selected as the isolation membrane.
[0177] 6) Assembly and formation are the same as in Example 1.
[0178] Example 6
[0179] 1) Manganese acetate, ferric acetate, sucrose / polyvinyl alcohol, lithium carbonate, and ammonium dihydrogen phosphate are mixed according to n(manganese acetate + ferric acetate), n(lithium carbonate), and n(ammonium dihydrogen phosphate) = 1:1:1, wherein n(manganese acetate): n(ferric acetate) satisfies 3:1, and deionized water is added and mixed, and then dried and crushed to obtain a precursor. The precursor is sprayed once and sintered in a nitrogen atmosphere to obtain a fired sample. The fired sample, carbon source, and deionized water are mixed and ball-milled, dried, crushed, sprayed twice, and then sintered twice in a nitrogen atmosphere to obtain manganese iron lithium phosphate agglomerate particles. The spray equipment pressure before the first and second firing is 0.6 MPa, and the amount of flux (potassium carbonate) added in the second spray drying before the second firing is 0.4%, and the dispersant (polyester polyether) is 0.25%.
[0180] 2) The positive electrode sheet was prepared in the same manner as in Example 1.
[0181] 3) The negative electrode sheet was prepared in the same manner as in Example 1.
[0182] 4) The preparation of the electrolyte is the same as in Example 1.
[0183] 5) Preparation of isolation film: PP / PF is selected as the isolation film.
[0184] 6) Assembly and formation are the same as in Example 1.
[0185] Comparative Example 1
[0186] 1) Preparation of positive electrode materials: Manganese acetate, iron acetate, sucrose / polyvinyl alcohol, lithium carbonate, and ammonium dihydrogen phosphate are mixed according to n(manganese acetate + iron acetate), n(lithium carbonate), and n(ammonium dihydrogen phosphate) = 1:1:1, where n(manganese acetate):n(iron acetate) satisfies 3:1, and then dried and crushed to obtain a precursor. After the precursor is sprayed once, it is sintered in a nitrogen atmosphere to obtain a sintered sample. After the sintered sample, carbon source, and deionized water are mixed and ball-milled, dried, crushed, and sintered in a nitrogen atmosphere after a second spray, and then crushed to obtain manganese iron lithium phosphate agglomerate particles. The pressure of the spray equipment before the first and second sintering is 1.12Mpa, and the amount of flux (potassium carbonate) added in the second spray drying before the second sintering is 0.25%, and the dispersant (polyester polyether) is 0.15%. The temperatures of the first and second sintering are 570 / 720℃, respectively, and the sintering time of the first sintering / second sintering is 9 / 10h.
[0187] 2) The positive electrode sheet was prepared in the same manner as in Example 1.
[0188] 3) The negative electrode sheet was prepared in the same manner as in Example 1.
[0189] 4) The preparation of the electrolyte is the same as in Example 1.
[0190] 5) Preparation of isolation membrane: PE is selected as the isolation membrane.
[0191] 6) Assembly and formation are the same as in Example 1.
[0192] Comparative Example 2
[0193] 1) Preparation of positive electrode materials: Manganese acetate, iron acetate, sucrose / polyvinyl alcohol, lithium carbonate, and ammonium dihydrogen phosphate are mixed according to n(manganese acetate + iron acetate), n(lithium carbonate), and n(ammonium dihydrogen phosphate) = 1:1:1, where n(manganese acetate): n(iron acetate) satisfies 3:1, and then dried and crushed to obtain a precursor. The precursor is sprayed once and sintered in a nitrogen atmosphere to obtain a sintered sample. The sintered sample, carbon source, and deionized water are mixed and ball-milled, dried, crushed, and sintered in a nitrogen atmosphere after a second spray. After crushing, lithium manganese iron phosphate agglomerate particles are obtained. The pressure of the spray equipment before the first and second sintering is 0.35Mpa, and the amount of flux (potassium carbonate) added in the second spray drying before the second sintering is 0.13%, and the dispersant (polyester polyether) is 0.2%. The temperatures of the first and second sintering are 450 / 665℃, respectively, and the sintering time of the first sintering / second sintering is 10 / 9h.
[0194] 2) The positive electrode sheet was prepared in the same manner as in Example 1.
[0195] 3) The negative electrode sheet was prepared in the same manner as in Example 1.
[0196] 4) The preparation of the electrolyte is the same as in Example 1.
[0197] 5) Preparation of isolation membrane: PE is selected as the isolation membrane.
[0198] 6) Assembly and formation are the same as in Example 1.
[0199] Other testing methods:
[0200] D90:
[0201] After turning the sample in the ziplock bag upside down 2-3 times, weigh about 0.04-0.06g of the sample and put it into a 50ml beaker;
[0202] Add 10ml 1% NP-40 sample dispersant to the beaker, stir with a glass rod during the addition process, then disperse with 40KHz external ultrasonic for 3 minutes, quickly pour all the dispersed samples into the particle size tester test sample pool, then rinse the beaker with a wash bottle, and pour all the rinse liquid into the sample pool. Set the sample refractive index and absorptivity in the instrument, the laser intensity ≥75%, and the instrument starts testing. After the test, the computer connected to the particle size test software will automatically output the particle size D90 data.
[0203] 2C constant current ratio:
[0204] Assemble the positive half-cell with the fresh positive electrode sheet, inject the liquid, package, and set the capacity of the assembled positive half-cell at room temperature, and complete the double charge test in a room temperature box. Double charge test (charge rate is 0.33C / 1 / 2C, 4.3V constant voltage charging, cut-off current 0.05C, and discharge rate is 0.33C), 2C charging steps: 2C constant rate charging to 4.3V, then 4.3V constant voltage charging, cut-off current 0.05C, and then 0.33C discharge. 2C constant current ratio = 2C constant rate charging capacity / 2C charging total capacity. The capacity in the current is the design capacity.
[0205] Energy density: Battery energy density = cell capacity × discharge platform ÷ cell volume
[0206] See Table 1, which shows the PD and PD max Specific test conditions
[0207] Table 1
[0208] Example One roll pressure Secondary rolling pressure Rolling temperature Roller speed Example 1 55bar 182bar 110℃ 8m / min Example 2 55bar 188bar 110℃ 8m / min Example 3 55bar 185bar 110℃ 8m / min Example 4 55bar 185bar 110℃ 8m / min Example 5 55bar 189bar 110℃ 8m / min Example 6 55bar 187bar 110℃ 8m / min Comparative Example 1 55bar 178bar 110℃ 8m / min Comparative Example 2 55bar 185bar 110℃ 8m / min
[0209] See Table 2, which shows some experimental parameters in the embodiments and comparative examples of the present invention.
[0210] Table 2
[0211] Process parameters Spray pressure before primary / secondary combustion Flux addition amount before second firing Amount of dispersant A added in the spray stage before the second calcination Primary sintering temperature One sintering time Carbon coating amount in one sintering Secondary sintering temperature Secondary sintering time Secondary sintering carbon coating amount unit MPa % % ℃ h % ℃ h % Example 1 0.4 0.1 0.05 550 8 0.25 640 9 1.8 Example 2 0.9 1.32 0.4 500 3 0.6 720 7 2.6 Example 3 0.65 0.3 0 540 9 0.35 660 8 1.9 Example 4 1.05 1.28 0.3 520 3 0.55 690 6 2.8 Example 5 0.82 1.4 0.8 545 6 0.4 760 7 2.2 Example 6 0.6 0.4 0.25 530 8 0.4 680 7 2.05 Comparative Example 1 1.12 0.25 0.15 570 9 0.58 720 10 3 Comparative Example 2 0.35 0.13 0.2 450 10 0.2 665 9 1.6
[0212] See Table 3, which shows the detection effect data in the embodiments of the present invention and the comparative examples.
[0213] Table 3
[0214] D90 PD σ Formula 1 Range △PD Formula 2 Range Performance 1 (2C constant current ratio) Performance 2 (square-shell battery energy density) Micrometer <![CDATA[g / cm 3 ]]> Mpa <![CDATA[micrometer × MPa / (g / cm 3 )]]> % <![CDATA[MPa×(g / cm 3 )]]> % Wh / L Parameter range 10-50 2.0~2.5 100~500 1600-4800 0~25 0-95 Example 1 49 2.05 150 3585 5% 7.50 60% 390 Example 2 11 2.39 400 1841 20% 80.00 56% 400 Example 3 42 2.15 170 3321 12% 20.40 69% 410 Example 4 14 2.32 360 2172 18% 64.80 65% 430 Example 5 25 2.45 420 4592 22% 92.40 59% 415 Example 6 38 2.20 230 4015 14% 32.20 74% 460 Comparative Example 1 12 2.3 300 1565 2.00% 6 46% 340 Comparative Example 2 31 2.15 395 5695 24.8% 97.96 36% 320
[0215] The above is a detailed introduction to a lithium manganese iron phosphate positive electrode sheet and a preparation method thereof, and a lithium ion battery provided by the present invention. Specific examples are used in this article to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enables any technician in the field to practice the present invention, including manufacturing and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified in a number of ways, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements that are not different from the text of the claims, or if they include equivalent structural elements that are not substantially different from the text of the claims, then these other embodiments should also be included in the scope of the claims.
Claims
1. A positive electrode sheet, characterized in that: The positive electrode sheet includes a current collector and a positive electrode material composited on the current collector; The positive electrode material includes a positive electrode active material; The positive electrode active material is selected from lithium manganese iron phosphate; The D90 particle size of the lithium manganese iron phosphate particles, the tensile strength σ of the positive electrode sheet, and the compaction density PD of the positive electrode sheet satisfy the relationship described in formula (I): 1600 <D90 / PD×σ<4800 (I); The unit of D90 is μm, the unit of σ is MPa, and the unit of PD is g / cm 3 ; The D90 particle size of the lithium iron manganese phosphate particles is 10-50 μm; The compacted density PD is 2.0-2.5 g / cm 3 ; The tensile strength σ is 100~500MPa.
2. The positive electrode sheet according to claim 1, characterized in that: In the formula (I), 2000 <D90 / PD×σ<4000。 3. The positive electrode sheet according to claim 1, characterized in that: The lithium iron manganese phosphate particles specifically include lithium iron manganese phosphate secondary particles.
4. The positive electrode sheet according to claim 1, characterized in that: The D90 particle size of the lithium iron manganese phosphate particles is 15-40 μm.
5. The positive electrode sheet according to claim 1, characterized in that: The compaction change rate ΔPD of the positive electrode sheet and the tensile strength σ of the positive electrode sheet satisfy the relationship described in formula (II): 0<σ×△PD<95 (II); Among them, the unit of σ is MPa, △PD=(PD max -PD) / PD, PD max is the maximum compaction density; The maximum compaction density is the compaction density corresponding to the positive electrode sheet when it is folded in half and transparent after secondary rolling.
6. The positive electrode sheet according to claim 5, characterized in that: The range of ΔPD is 4% to 25%.
7. A lithium ion battery, characterized in that: Including positive electrode; The positive electrode sheet is the positive electrode sheet according to any one of claims 1 to 6.
Citation Information
Patent Citations
Coil type battery plate group and battery comprising the same
CN101339983A
Manganese-iron-lithium phosphate material and preparation method thereof, battery paste, cathode and lithium battery
CN106816582A